2020
DOI: 10.1080/13527266.2020.1759120
|View full text |Cite
|
Sign up to set email alerts
|

The impact of review valence and awareness of deceptive practices on consumers’ responses to online product ratings and reviews

Abstract: Many online retailers and some manufacturers/service providers have recently been engaging in questionable practices, where product reviews are often fabricated and/or posted without sufficient clarity and objectivity. Across an exploratory study and two main studies, we empirically examine this phenomenon and observe a pattern of effects that suggests that review valence (i.e., the average number of rating-stars a product receives) influences product attitudes and intentions, but that these outcomes are signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…First, rating valence has a significant effect on purchase intention. These results are similar to other recent studies conducted (Karabas et al 2021 ; Maslowska et al 2017 ; Von Helversen et al 2018 ; Yang et al 2016 ). The current study was not only limited to a comparison with the amount of WOM (Chintagunta et al 2010 ; Gopinath et al 2014 ) but also showed the magnitude of the influence of rating valence when compared with the rating distribution.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…First, rating valence has a significant effect on purchase intention. These results are similar to other recent studies conducted (Karabas et al 2021 ; Maslowska et al 2017 ; Von Helversen et al 2018 ; Yang et al 2016 ). The current study was not only limited to a comparison with the amount of WOM (Chintagunta et al 2010 ; Gopinath et al 2014 ) but also showed the magnitude of the influence of rating valence when compared with the rating distribution.…”
Section: Discussionsupporting
confidence: 93%
“…Next, in rating valence, the following two viewpoints were considered. First, WOM reviews with 4.2 stars are more likely to influence purchase than perfect 5-star ones, as stated above (Karabas et al 2021 ; Maslowska et al 2017 ). Second, EC platforms use product information and accumulated WOM data to recommend products that are presumed to be easy to purchase and are present at the top of the search page (Barton, 2006 ; Liu and Pang 2018 ; Lin 2014 ).…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations